2012
DOI: 10.1128/jvi.00581-12
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Lysine 4 Methylation Marks Postreplicative Human Cytomegalovirus Chromatin

Abstract: In the nuclei of permissive cells, human cytomegalovirus genomes form nucleosomal structures initially resembling heterochromatin but gradually switching to a euchromatin-like state. This switch is characterized by a decrease in histone H3 K9 methylation and a marked increase in H3 tail acetylation and H3 K4 methylation across the viral genome. We used ganciclovir and a mutant virus encoding a reversibly destabilized DNA polymerase to examine the impact of DNA replication on histone modification dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Our prior work has demonstrated that nucleosomes are not confined to cellular chromatin but also form on hCMV nuclear DNA (87)(88)(89). We have also recently shown that global nucleosome occupancy and dynamics across hCMV genomes are largely controlled by IE1-dependent mechanisms (88).…”
Section: Figmentioning
confidence: 96%
“…Our prior work has demonstrated that nucleosomes are not confined to cellular chromatin but also form on hCMV nuclear DNA (87)(88)(89). We have also recently shown that global nucleosome occupancy and dynamics across hCMV genomes are largely controlled by IE1-dependent mechanisms (88).…”
Section: Figmentioning
confidence: 96%
“…Activating histone H3K9 and H3K14 acetylations are found at IE promoters as early as 3-6 h postinfection (hpi), prior to the acetylation at E or L promoters (4). Methylated H3K4, another activating mark, is incorporated into viral chromatin following its replication (5). Importantly, this study demonstrated selective epigenetic tagging of HCMV versus cellular chromatin.…”
mentioning
confidence: 87%
“…Following reactivation, when IE1 is expressed, histones associated with the MIEP are acetylated, resembling transcriptionally active euchromatin (15,16). This mechanistically parallels the onset of lytic infection where, prior to IE gene expression, viral genomes show heterochromatic features, whereas later, when IE genes are being expressed, they are euchromatic (21)(22)(23).…”
mentioning
confidence: 88%